College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.8 - Solving Basic Equations - P.8 Exercises - Page 60: 37



Work Step by Step

$(x-1)(x+2)=(x-2)(x-3)\displaystyle$ We distribute both sides: $x^{2}+x-2=x^{2}-5x+6$ And simplify: $x-2=-5x+6$ And combine $x$ terms: $6x=8$ And solve for $x$: $x=\frac{4}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.